1998
DOI: 10.1002/j.1550-8528.1998.tb00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Insulin Concentrations, Smoking, and Alcohol Intake Are Important Independent Predictors of Leptin in Young Healthy Men

Abstract: MANTZOROS, CHRISTOS S., ANTONIOS D. LIOLIOS, NICHOLAS A. TRITOS, VIRGINIA G. KAKLAMANI, DIMITRIOS E. DOULGERAKIS, IOANNIS GRIVEAS, ALAN C. MOSES, JEFFREY S. FLIER. Circulating insulinconcentrations, smoking, and alcohol intake are important independent predictors of leptin in young healthy men. Obes Res. 1998;6:179-186. Objective: Leptin, an adipocyte-secreted hormone, has been shown to signal the status of energy stores to the brain, regulate energy homeostasis, and mediate the neuroendocrine response to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
80
1
6

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 75 publications
11
80
1
6
Order By: Relevance
“…Lower leptin levels were also observed, consistent with previously reported findings, 16) although conflicting results have been reported. Leptin is a 26-kDa protein secreted primarily from adipocytes, and suppresses food intake and increases energy expenditure by enhancing thermogenesis and increasing the metabolic rate in humans.…”
Section: Discussionsupporting
confidence: 91%
“…Lower leptin levels were also observed, consistent with previously reported findings, 16) although conflicting results have been reported. Leptin is a 26-kDa protein secreted primarily from adipocytes, and suppresses food intake and increases energy expenditure by enhancing thermogenesis and increasing the metabolic rate in humans.…”
Section: Discussionsupporting
confidence: 91%
“…52,53 Some studies have shown that higher alcohol consumption is associated with total energy intake 54 and favors fat storage and weight gain, 55 which may increase adipocyte Dietary and lifestyle factors and plasma leptin levels N-F Chu et al mRNA expression of leptin. 36 Our results do not indicate an association between alcohol intake and plasma leptin concentrations overall or in either normal weight or overweight men. Alcohol intake does not seem to be a major modulator of energy intake and leptin production.…”
Section: Discussioncontrasting
confidence: 81%
“…52,53 Furthermore, smoking may be associated with an increase in leptin sensitivity. 35,36 The higher leptin concentrations among past smokers could be a marker of loss of leptin sensitivity. This could explain, in part, the usual weight gain that accompanies smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been argued that this relationship was not clear evidence of resistance to leptin but rather an adaptative attempt to oppose other forces promoting obesity (Arch et al, 1998). Excess leptin may provide indirect information about behavioral aspects related to adiposity gain, such as a lack of physical activity, overfeeding (Kolaczynski et al, 1996) or alcohol consumption (Mantzoros et al, 1998). Our results show a negative association between plasma leptin and physical activity.…”
Section: Discussionmentioning
confidence: 50%